Nutrition essentials for nursing practice - Dudek, Susan G. (Philadelphia, Pennsylvania : Lippincott Williams & Wilkins, 2006)
"With new features like the Career Connection, this revised edition illustrates the relevance of nutrition in real-world nursing. In conjunction with current research that reflects the latest science-based practice, including AHA recommendations, growth charts, and NCEP guidelines, Nutrition Essentials for Nursing Practice, 5th Edition will prepare nursing students to think on their feet and apply nutritional expertise with confidence."--Jacket
Unit one: Principles of nutrition -- Nutrition in nursing -- Carbohydrates -- Protein -- Lipids -- Vitamins -- Water and minerals -- Energy metabolism -- Unit two: Nutrition in health promotion -- Guidelines for healthy eating -- Consumer issues -- Cultural and religious influences on food and nutrition -- Healthy eating for healthy babies -- Nutrition for infants, children, and adolescents -- Nutrition for adults and older adults -- Unit three: Nutrition in clinical practice -- Obesity and eating disorders -- Feeding patients: hospital food and enteral and parenteral nutrition -- Critical illness and hypermetabolic conditions -- Nutrition for patients with gastrointestinal disorders -- Nutrition for patients with cardiovascular disorders -- Nutrition for patients with diabetes mellitus -- Nutrition for patients with renal disorders -- Nutrition for patients with cancer or HIV/AIDS
Includes bibliographical references and index.
Keywords: DIET THERAPY